Impulsivity of Noise due to Single Lightweight Vehicles Transit on Transverse Rumble Strip - Darus N.; Haron Z.; Yahya K.; Abd Halil M.H.; Norudin W.M.A.; Othman M.H.; Hezmi M.A. (E3S Web of Conferences, 2018)
Transverse Rumble Strips (TRS) acts as safety device that alert inattentive drivers from potential dangers. However, the noise produced due to TRS was reported as noise annoyance among the nearby residents lived adjacent to roadways. Thus, this paper investigates the impulsivity characteristic of noise due to single lightweight vehicles transit on TRS. The objectives of this study are to determine the increase of sound level and to evaluate the impulsivity of noise. Two TRS profiles namely middle overlapped (MO) and middle layer overlapped (MLO) were selected. Three types of single lightweight vehicles which include hatchback, sedan and multipurpose (MPV) were tested at speed of 30, 50 and 70km/h. The sound level was measured using sound level meter (SLM). Noise indices such as LAeq, LAIeqT, LAImax, LAFmax and LASmax were obtained from the measurement. This study considered the differences of LAImax – LAFmax > 2dBA, LAFmax – LAeq ≥ 10dBA, LAIeqT – LAeq ≥ 2dBA and LAImax – LASmax > 6dBA to evaluate the impulsivity of noise. It was found that TRS increased the sound level by at most of 6dBA. Furthermore, all single lightweight vehicles transit on TRS show significant impulsive characteristic. These results proved that TRS produce significant impact to the nearby residents.